Automatic Quality Assessment of Smart Device Microphone Spirometry - A. Fonseca, J. (2020)
Lung function tests are critical for diagnosis and monitoring of asthma and other respiratory diseases. Monitoring of lung function, in the absence of a healthcare professional, is very challenging but may be obtained through Smart Devices if automated quality assessment systems guarantee the proper technique during the forced expiratory manoeuvre. This paper describes the evaluation of one such system that uses the microphone of smart devices, regarding the initial effort of forced expiratory manoeuvres using the Back Extrapolated Volume. A health professional recorded microphone spirometry in 55 children (5-10 years), using a mobile game engineered for the purpose, and registered its quality. At least one acceptable manoeuvre was achieved for 96% of the children using a featured threshold. Using a stricter threshold of 5% of forced vital capacity, it was possible to ensure at least one acceptable manoeuvre for 69%. While the obtained results are comparable to findings in literature for regular spirometry in this age group, further work is required before we can determine whether the proposed algorithm is effective in real life.